Foucault against management: Thinking differently about the foundations and future of management studies - Cummings, Stephen (School of Management Working Papers, 2002)
Management studies must seek a greater association with its history. But only by also thinking critically about the historical assumptions that already pervade our field, might we increase the possibility of thinking differently for the future and get full benefit from this association. Counter-historian Michel Foucault never analyzed management directly, but his approaches can be effectively utilized to interrogate the historical assumptions upon which management studies is based, how these roots may limit us in the present and how we might think otherwise. This paper offers a synopsis of Foucault’s ideas and how they might be applied, and two illustrations of their utility: the first examines the invention of management; the second deconstructs management’s assumed disciplinary foundations.